Perspectives@25 : a quarter century of new art in Houston - Contemporary Arts Museum, Houston (Houston : Contemporary Arts Museum Houston, 2004)
Adler, Amy ; Amer, Ghada ; Anderson, Laurie ; Attie, Dotty ; Biggers, Sanford ; Bischoff, Elmer ; Blake, Nayland ; Bleckner, Ross ; Block, Gay ; Bloom, Suzanne ; Boltanski, Christian ; Borland, Christine ; Bradford, Mark ; Burson, Nancy ; Calle, Sophie ; Close, Chuck ; Coe, Sue ; Condo, George ; Crotty, Russell ; Cruzvillegas, Abraham ; Douglas, Stan ; Doyle Hancock, Trenton ; Drake, James ; Engelstein, Sharon ; Eno, Brian ; Essenhigh, Inka ; Fischl, Eric ; Fisher, Vernon ; Glass, Philip ; Goldin, Nan ; Graham, Rodney ; Hesse, Eva ; Hill, Ed ; Hill, Gary ; Holzer, Jenny ; Huerta, Benito ; Johnson, Lucas ; Kay, Emma ; Kendrick, Mel ; Kruger, Barbara ; Kubricht, Charles Mary ; Kuitca, Guillermo ; Lawrence, Annette ; Lichtenstein, Roy ; Longo, Robert ; McCracken, John ; McGee, David ; Miller, Melissa ; Morimura, Yasumasa ; Neto, Ernesto ; Nicosia, Nic ; Ono, Yoko ; Parazette, Aaron ; Pfeiffer, Paul ; Price, Ken ; Ranta, Rachel ; Rauch, Neo ; Rauschenberg, Robert ; Robleto, Dario ; Rodriguez, Lordy ; Rosmarin, Susie ; Roth, Alan ; Sandström, Sigrid ; Sherman, Cindy ; Sidén, Ann-Sofi ; Simpson, Lorna ; Sontheimer, Matthew ; Souza, Al ; Stack, Gael ; Staley, Earl ; Tansey, Mark ; Taylor-Wood, Sam ; Utterback, Robin ; Ward, Liz ; Weems, Carrie Mae ; Wegman, William ; Wilson, Ann ; Ziebell, Robert
Perspectives Artists 1979-2004 p. 181-185
Perspectives Chronology p. 186-200
Engels
Exhibition. Perspectives@25 : A quarter century of new art in Houston. Contemporary Arts Museum Houston. 2004-10-16. 2005-01-09
boek